Invasão cultural: uma experiência de vocalização do texto poético - Santos, Laercio Fernandes dos (2020)
The core of this investigation is the experience of vocalizing written poetic texts within a language experience project entitled Invasão Cultural. It is a reflection derived from the Benvenistian principle according to which language is performed in an instance of discourse, that emanates from a speaker, a sound form that reaches a listener and brings about another enunciation in return. The mention of the sound form motivates the following question: What do students say about their experience of vocalizing the poetic text, a language experience undergone in the Invasão Cultural Project? To answer this question, the present investigation is based on the following enunciative relationships: a) speaker to language, b) speaker to language in the poetic instance, and c) speaker to someone else. The study finds its justification in the adoption of Benveniste’s work perspective, centered in the search for the elucidation of the concepts and principles that define enunciation as the experience of mankind with language. In addition, this research is supported by recently developed studies on the vocal aspect of language, among which is the concept of vocal arrangement, by Diedrich (2015); and vocalization by Juchem (2017), works that are focused on the notion of voicing as one of the aspects of enunciation. The research is anchored in the idea that, in the act of vocalizing poetry, the speaker takes ownership of the text and assumes, through particular vocal arrangements, the role of a subject, thus renovating the discourse. By using special vocal arrangements in this act of appropriation, the speaker takes over the place of saying and introjects another one before himself. These relationships of a speaker to language, a speaker to language in the poetic instance, and a speaker to someone else reveal the updating of meaning, and raises, alongside a material structure, an immaterial structure, the communication of meanings, replacing events or experiences by their evocation. The aim here is to reflect on the analysis of statements of the students who were protagonists in such enunciative acts about their experience in vocalizing poetic texts within the Invasão cultural project, a language-learning experience. Thus, this study is focused on the notion of enunciation, but it turns to the great field of language, and the experience of mankind with language by the relation of meanings that impel from poetry vocalization. The investigation is justified by two guiding elements: the first is directly linked to the researcher's pedagogical practice, which is marked by the work with language in its poetic manifestation via vocalization; the second concerns the possibility of conceiving the teaching of language and literature through an enunciative approach. To this end, the statements extracted from The Invasão Cultural Project (Passo Fundo - RS) are hereby analyzed. The aforementioned project is characterized by the performance of High School students who, following their teacher's guidance, take ownership of written poetic texts by particular vocalizations before a certain audience. In this way, this research finds its double importance: it potentially deepens and expands studies around the proposed theoretical notions; and it presents itself as a possibility of qualifying the teaching of language and literature at school. The results achieved indicate that the experience of vocalizing poetry elicits particular meanings experienced in the historicity of the subject with their language and plays an important role in the constitution of students in language and literature classes.